A method for improving the transparency of silicon carbide crystal surface
By applying and curing the resin solution with a suitable refractive index on the surface of the silicon carbide crystal, a transparent resin film is formed, which solves the problem of opacity on the surface of the silicon carbide crystal and realizes an efficient and low-cost detection method.
Patent Information
- Application Number
- CN202210917570.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-01
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-08-01
AI Technical Summary
Microtubes and enclosure defects are common in silicon carbide crystals, resulting in opaque surfaces and difficult to detect by optical microscope. The existing detection methods are costly and inefficient.
By preparing a resin solution with a refractive index suitable for silicon carbide crystals, it is applied to the surface of silicon carbide crystals, and cured to form a transparent resin film to improve the transparency of the crystal surface.
The surface transparency of silicon carbide crystals is improved, the detection process is simplified, the processing cost is reduced, and the detection efficiency is improved.
Smart Images

Figure CN115266755B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of silicon carbide crystal detection, and in particular to a method for improving the surface transparency of a silicon carbide crystal. Background Art
[0002] Microtubes and inclusion defects are common in silicon carbide crystals grown by the PVT (Physical vapor transmission) method. Microtubes may directly affect the quality of the epitaxial layer, and inclusions may also affect the stability of the final device due to the presence of impurities. Since such defects exist inside the crystal and the defect size is between macroscopic and microscopic, the detection method is generally to use strong light combined with microscope observation, which requires that the surface of the silicon carbide crystal being tested has a certain degree of transparency in the visible light range. When the silicon carbide crystal is opaque, when the electromagnetic wave passes through two media with different refractive indices, projection, refraction and reflection occur at the junction of the two media. Since the surface roughness, flatness and other surface shape indicators of the crystal that has not been precisely polished are relatively poor, complex refraction and reflection will occur.
[0003] A domestic enterprise has proposed a convenient inclusion detection solution CN216082537U. In order to achieve the perspective detection effect, the crystal must be ground and polished; CN110361139B uses other methods to detect large-sized microtubes. Although visible light detection can be avoided, there may be large errors for thicker samples or microtubes with smaller diameters. Due to the physical properties of silicon carbide single crystals, although there are some processing methods such as CN114388347A, the grinding and polishing costs are high. On the other hand, once the test results show that there are too many microtubes or inclusions, the product can only be downgraded or even scrapped, and the high cost of the previous processing causes waste.
[0004] In view of the above situation, there is an urgent need for a method that can quickly detect the internal quality of silicon carbide crystals with only rough processing. Summary of the invention
[0005] In view of the above shortcomings of the prior art, the present invention provides a method for improving the surface transparency of a silicon carbide crystal, so as to improve the problem of high cost and serious waste in the previous processing.
[0006] To achieve the above-mentioned purpose and other related purposes, the present invention provides a method for improving the surface transparency of a silicon carbide crystal, comprising the following steps: providing a silicon carbide crystal; preparing a resin solution whose refractive index matches the refractive index of the silicon carbide crystal; applying the resin solution to the surface of the silicon carbide crystal to form a resin layer on the surface of the silicon carbide crystal; and curing the resin layer to form a transparent resin film on the surface of the silicon carbide crystal.
[0007] In one embodiment of the present invention, the steps of preparing a resin solution having a refractive index that matches the refractive index of the silicon carbide crystal are as follows: placing phenyltrimethoxysilane and methyl isobutyl ketone in a reaction container according to a certain mass ratio, and maintaining the temperature of the reaction container at -5 to 5°C; adding a mixture of pure water, hydrochloric acid and tetrahydrofuran in a certain mass ratio dropwise into the reaction container, stirring for 20 to 120 minutes, so that the above components are evenly mixed, wherein the stirring speed is controlled at 1 to 100 rpm; introducing an inert gas into the reaction container, and at the same time raising the temperature of the reaction container to 30 to 90°C, so that it reacts for 1 to 10 hours under the protection of an inert atmosphere; adding a mixture of tetrabutyl titanate and tetrahydrofuran in a certain mass ratio dropwise into the reaction container, and the time is controlled at 1 to 10 hours to obtain a mixed solution; dispersing a nano-metal compound filler having a mass of 0.1% to 10% of the mass of the mixed solution into the reaction container, stirring evenly, and obtaining a resin solution.
[0008] In one embodiment of the present invention, the mass ratio of phenyltrimethoxysilane to methyl isobutyl ketone is 1:2-1:8; the mass ratio of pure water, hydrochloric acid and tetrahydrofuran is 1:(0.1-1):(2-10); the mass ratio of tetrabutyl titanate to tetrahydrofuran is 1:2-1:8; and the pH value of the resin solution is 1-3.
[0009] In one embodiment of the present invention, the steps of applying the resin solution to the surface of the silicon carbide crystal are as follows: placing the silicon carbide crystal on a coating machine; dripping the resin solution onto the surface of the silicon carbide crystal to form a resin layer on the surface of the silicon carbide crystal; wherein, during the coating process, the rotation speed of the coating machine is controlled at 5000 to 15000 rpm.
[0010] In one embodiment of the present invention, the step of applying the resin solution to the surface of the silicon carbide crystal is as follows: the step of curing the resin layer is as follows: placing the silicon carbide crystal coated with the resin layer in a vacuum environment of 0.1 to 0.001 Pa, and standing at a temperature of 50 to 150°C for 1 to 10 hours; then raising the temperature to 200 to 500°C, and curing for 1 to 10 hours with the assistance of ultraviolet light to form a transparent resin film on the surface of the silicon carbide crystal.
[0011] In one embodiment of the present invention, the nano metal compound is any one or more of titanium oxide, zirconium oxide, lead sulfide and zinc sulfide, and the particle size of the nano metal compound is 1 to 50 nm.
[0012] In one embodiment of the present invention, the refractive index of the mixed solution is 1.7-2.1.
[0013] In one embodiment of the present invention, the refractive index of the resin solution is 1.75-2.75.
[0014] In one embodiment of the present invention, the transparent resin film on the surface of the silicon carbide has a refractive index of 1.8 to 2.7, a thickness of 0.01 to 5 mm, and a light transmittance of 75 to 88% within a wavelength range of 400 to 700 nm.
[0015] In one embodiment of the present invention, the transparent resin film is tightly combined with the silicon carbide crystal and the area without pores is more than 75% of the area covered by the resin film.
[0016] The present invention provides a method for improving the transparency of the surface of a silicon carbide crystal. Phenyl trimethoxysilane, methyl isobutyl ketone, tetrahydrofuran, tetrabutyl titanate and hydrochloric acid are used as raw materials, and then a nano metal compound is added after hydrolysis and condensation to prepare a resin solution that matches the refractive index of the silicon carbide crystal. The resin solution is coated on the surface of the silicon carbide crystal to form a resin layer. The resin layer is cured to form a transparent resin film on the surface of the silicon carbide crystal. The refractive index of the transparent resin film matches the silicon carbide crystal to avoid complex refraction and reflection when electromagnetic waves propagate between the resin and the crystal. The present invention improves the transparency of the surface of the silicon carbide crystal by a simple method, which is conducive to accelerating the efficiency of detecting internal defects of the crystal using an optical microscope and avoiding unnecessary processing costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 A flow chart showing a method for improving the surface transparency of a silicon carbide crystal according to the present invention;
[0019] Figure 2 Shown is a flow chart of a method for preparing a resin solution in one embodiment of the present invention;
[0020] Figure 3 Shown is a flow chart of a resin layer curing process in one embodiment of the present invention;
[0021] Figure 4 A schematic diagram of a silicon carbide crystal with high transparency produced in one embodiment of the present invention is shown.
[0022] Component number description
[0023] 1. Silicon carbide crystal; 2. Rough layer; 3. Transparent resin film. DETAILED DESCRIPTION
[0024] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.
[0025] It should be noted that the terms such as "upper", "lower", "left", "right", "middle" and "one" etc. used in this specification are only for the convenience of description and are not intended to limit the scope of implementation of the present invention. Changes or adjustments to their relative relationships, without substantially changing the technical content, should also be regarded as the scope of implementation of the present invention.
[0026] See also Figure 1 The present invention provides a method for improving the surface transparency of a silicon carbide crystal, which specifically comprises the following steps:
[0027] S1. providing a silicon carbide crystal;
[0028] S2, preparing a resin solution having a refractive index that matches the refractive index of the silicon carbide crystal;
[0029] S3, applying the resin solution to the surface of the silicon carbide crystal to form a resin layer on the surface of the silicon carbide crystal;
[0030] S4, curing the resin layer to form a transparent resin film on the surface of the silicon carbide crystal.
[0031] See also Figure 1 and Figure 4 The silicon carbide crystal 1 in step S1 is a silicon carbide crystal that has not been polished and has a rough layer 2 on its surface. The refractive index of a conventional silicon carbide crystal is 2.6.
[0032] See also Figure 1 and Figure 2 Step S2 of preparing the resin solution specifically comprises:
[0033] S21, placing phenyltrimethoxysilane and methyl isobutyl ketone in a reaction container according to a certain mass ratio, and maintaining the temperature of the reaction container at -5 to 5° C.;
[0034] S22, adding a mixture of pure water, hydrochloric acid and tetrahydrofuran in a certain mass ratio dropwise into the reaction container, stirring for 20 to 120 minutes to mix the above components evenly;
[0035] S23, introducing an inert gas into the reaction container, and raising the temperature of the reaction container to 30-90° C., allowing the reaction to proceed for 1-10 hours under the protection of an inert atmosphere;
[0036] S24, adding a mixed solution of tetrabutyl titanate and tetrahydrofuran in a certain mass ratio dropwise into the reaction container, and controlling the reaction time to be 1 to 10 hours to obtain a mixed solution;
[0037] S25, dispersing nano-metal compound fillers whose mass is 0.1% to 10% of the mass of the mixed solution into the reaction container, stirring the mixture thoroughly and evenly to obtain a resin solution.
[0038] In step S21, the mass ratio of phenyltrimethoxysilane to methyl isobutyl ketone is 1:2 to 1:8, for example, it can be any mass ratio within the above range such as 1:2, 1:4, 1:6 or 1:8. Phenyltrimethoxysilane and methyl isobutyl ketone are placed in a reaction container according to the above ratio, and the temperature is maintained at -5 to 5°C. For example, the temperature of the reaction container can be any value within the above range such as -5°C, -2°C, 0°C, 3°C, 5°C. The above reaction container is a container resistant to organic corrosion, for example, it can be a glass container, of course, it can also be a container of other materials, which is not limited here.
[0039] In step S22, the mass ratio of pure water, hydrochloric acid and tetrahydrofuran is 1: (0.1-1): (2-10), for example, it can be any mass ratio within the above range such as 1: 0.1: 2, 1: 0.1: 10, 1: 1: 10, 1: 0.5: 6, etc. Pure water, hydrochloric acid and tetrahydrofuran are placed in the reaction container in S21 according to the above ratio, and stirred for 20-120 minutes, for example, the stirring time can be any value within the above range such as 20 minutes, 50 minutes, 90 minutes or 120 minutes; the stirring speed is controlled at 1-100 rpm, for example, the stirring speed can be any value within the above range such as 1 rmp, 10 rmp, 50 rmp, 80 rmp or 100 rmp.
[0040] In step S23, the temperature of the reaction container is raised to 30-90°C, and the reaction is carried out for 1-10 hours under the protection of an inert atmosphere. For example, the temperature of the reaction container can be any value within the above range, such as 30°C, 60°C, 90°C, etc.; the reaction time can be any value within the above range, such as 1h, 3h, 5h, 8h or 10h.
[0041] In step S24, the mass ratio of tetrabutyl titanate to tetrahydrofuran is 1:2 to 1:8, for example, it can be any value within the above range such as 1:2, 1:4, 1:6 or 1:8. The reaction time is controlled to be 1 to 10 hours, for example, the reaction time can be any value within the above range such as 1 hour, 3 hours, 5 hours, 8 hours or 10 hours. The pH value of the mixed solution is 1 to 3, for example, the pH value of the mixed solution can be any value within the above range such as 1, 1.5, 2.5 or 3. The refractive index of the obtained mixed solution is 1.7 to 2.1, for example, the refractive index of the mixed solution can be any value within the above range such as 1.7, 2 or 2.1.
[0042] In step S25, the nano metal compound is dispersed into the mixed solution obtained in step S24, and stirred evenly to obtain a resin solution, wherein the mass of the nano metal compound is 0.1% to 10% of the mass of the mixed solution. The mass fraction of the nano metal compound can be any value within the above range of 0.1%, 1%, 3%, 7% or 10%; the particle size of the nano metal compound is 1 to 50nm, for example, it can be any value within the above range of 1nm, 10nm, 30nm or 50nm. The nano metal compound includes any one or more of titanium oxide, zirconium oxide, lead sulfide and zinc sulfide, for example, the nano metal compound is titanium oxide, or zirconium oxide, or lead sulfide, or zinc sulfide, or a combination of zirconium oxide and lead sulfide, or a combination of titanium oxide and zirconium oxide, etc., which are not listed one by one here. When the metal compound is a combination of several components, there is no restriction on the proportion of each component in the composition, and it can be mixed in any proportion. The refractive index of the resin solution obtained in step S25 is 1.75-2.75. For example, the refractive index of the resin solution can be any value within the above range, such as 1.75, 2, 2.5 or 2.75.
[0043] See also Figure 1 , step S3 of applying the resin solution to the surface of the silicon carbide crystal is as follows: placing the silicon carbide crystal on a coating machine; dripping the resin solution onto the surface of the silicon carbide crystal to form a resin layer on the surface of the silicon carbide crystal. During the coating process, the speed of the coating machine is controlled at 5000 to 15000 rpm. For example, the speed of the coating machine can be any value within the above range such as 5000 rpm, 8000 rpm, 12000 rpm or 15000 rpm. After coating, the silicon carbide crystal with the resin layer can be directly applied to some scenarios. Preferably, the resin layer is cured to form a transparent resin film.
[0044] See also Figure 1 and Figure 4 The step of curing the resin layer in S4 includes:
[0045] S41, placing the silicon carbide crystal coated with the resin layer in a vacuum environment of 0.1 Pa to 0.001 Pa, and leaving it to stand at a temperature of 50 to 150° C. for 1 to 10 hours;
[0046] S42, raising the temperature to 200-500°C, and curing for 1-10 hours with the assistance of ultraviolet light to form a transparent resin film on the surface of the silicon carbide crystal.
[0047] In step S41, the pressure of the vacuum environment can be any value within the above range, such as 0.1Pa, 0.005Pa, 0.002Pa or 0.001Pa; the temperature can be any value within the above range, such as 50℃, 70℃, 100℃, 130℃ or 150℃; the standing time can be any value within the above range, such as 1h, 3h, 8h or 10h.
[0048] In step S42, the temperature can be any value within the above range, such as 200°C, 300°C, 400°C or 500°C; the curing time can be any value within the above range, such as 1h, 4h, 6h, 9h or 10h.
[0049] See also Figure 1 and Figure 4 Since the silicon carbide crystal 1 has not been subjected to grinding and polishing treatment, its surface has a rough layer 2. The present invention improves the transparency of the rough surface of the silicon carbide crystal by preparing a transparent resin film 3 that matches the refractive index of the silicon carbide crystal 1 on the surface of the rough layer 2. The refractive index of the transparent resin film is 1.8-2.7, the thickness is 0.01-5mm, and the numerical layer transmittance is 75-88% within the wavelength range of 400-700nm. For example, the coverage area can be any value within the above range such as 75%, 80%, 95% or 100%; the refractive index of the transparent resin film 3 can be any value within the above range such as 1.8, 2.0, 2.5 or 2.7; the thickness of the transparent resin film 3 can be any value within the above range such as 0.01mm, 1mm, 3mm or 5mm; the transmittance of the resin film within the wavelength range of 400-700nm can be any value within the above range such as 75%, 80%, 85% or 88%. Preferably, the area where the transparent resin film 3 is tightly combined with the silicon carbide crystal 1 and has no pores is more than 75% of the area covered by the transparent resin film 3 .
[0050] The present invention is further described below through several examples, and the chemical reagents used in the following examples can all be obtained through commercial means. Under different test conditions, the pre-treatment of the surface of the silicon carbide crystal when the resin is coated is different.
[0051] Example 1
[0052] See also Figure 1 to Figure 4In this experiment, EPD (etchpit density) analysis is performed on silicon carbide crystals. The samples need to be ground and polished to make the crystals transparent. If the defects exceed the standard, the crystals will be downgraded or even scrapped. The previous grinding and polishing costs are wasted. Therefore, the method of the present invention is used to improve the transparency of the silicon carbide crystal surface. The sample preparation steps are as follows:
[0053] 1) Phenyltrimethoxysilane and methyl isobutyl ketone were placed in a glass reaction container at a mass ratio of 1:3, and the temperature of the reaction container was maintained at 0°C.
[0054] 2) Pure water, hydrochloric acid and tetrahydrofuran were added dropwise into the reaction vessel at a mass ratio of 1:0.2:5, and stirred at 50 rpm for 60 min.
[0055] 3) N is introduced into the reaction vessel. 2 , while raising the temperature of the reaction vessel to 65°C, N 2 The reaction was carried out under atmosphere protection for 2 h.
[0056] 4) Tetrabutyl titanate and tetrahydrofuran in a mass ratio of 1:5 were added dropwise into the reaction container and maintained for 8 hours to obtain a mixed solution with a pH of 1.
[0057] 5) Ultrasonic dispersion of zinc sulfide with a particle size of 1.2 nm, which is 1% of the mass of the mixed solution, and zinc sulfide with a particle size of 2.2 nm, which is 0.1% of the mass of the mixed solution, is added to a reaction container and stirred evenly to obtain a resin solution.
[0058] 6) Cut a single crystal silicon carbide wafer with a diameter of 151 mm and a thickness of 2 mm using a single wire, remove the processing liquid on the surface by ultrasonic cleaning, and dry. Put the wafer into a mixed solution of KOH and NaOH at 80°C and etch for 20 minutes to obtain an etched sample. Among them, the ratio of KOH and NaOH in the mixed solution of KOH and NaOH can be set according to the ratio of conventional etching solution when etching silicon carbide crystals in the art.
[0059] 7) Place the etched sample on a coating machine, control the rotation speed of the coating machine at 5000 rpm, and drip the resin solution onto the etched sample to form a resin layer on the surface of the silicon carbide crystal.
[0060] 8) The silicon carbide crystal coated with the resin layer was placed in a vacuum environment of 0.001 Pa and allowed to stand at 90° C. for 10 hours; the temperature was raised to 260° C. with the assistance of ultraviolet light and cured for 2 hours, and a transparent resin film with a thickness of 0.85 mm was formed on the surface of the silicon carbide crystal.
[0061] 9) Place the other side of the corrosion sample on the coating machine, repeat the steps 7) and 8) and then send it to the optical microscope for defect analysis. Figure 4 As shown, in step 6), an etching layer is formed on the rough layer 2 on the surface of the silicon carbide crystal 1, and the transparent resin film 3 is located on the outer layer of the rough layer 2.
[0062] Since the resin film is relatively flat, the sample transmittance is about 78% in the visible light range, and the sample surface is flat, which is convenient for focusing analysis with an optical microscope.
[0063] Example 2
[0064] See also Figure 1 to Figure 4 This experiment analyzes the internal inclusion defects of N-doped silicon carbide substrates. Although the sample thickness is only 300μm to 500μm, the doped crystal has a certain absorption effect on visible light, so the sample needs to be ground and polished to make the crystal transparent. If the defects exceed the standard, the crystal will be downgraded or even scrapped. The previous grinding and polishing will cause cost waste, so the method of the present invention is used to improve the transparency of the silicon carbide crystal surface. The sample preparation steps are as follows:
[0065] 1) Phenyltrimethoxysilane and methyl isobutyl ketone were placed in a glass reaction container at a mass ratio of 1:3, and the temperature of the reaction container was maintained at 1°C.
[0066] 2) Pure water, hydrochloric acid and tetrahydrofuran were added dropwise into the reaction vessel at a mass ratio of 1:0.25:5, and stirred at 100 rpm for 50 min.
[0067] 3) N is introduced into the reaction vessel. 2 , while raising the temperature of the reaction vessel to 60°C, N 2 The reaction was carried out under atmosphere protection for 2 h.
[0068] 4) Tetrabutyl titanate and tetrahydrofuran in a mass ratio of 1:5 were added dropwise into the reaction container and maintained for 8 hours to obtain a mixed solution with a pH of 1.
[0069] 5) 1.1% by weight of the mixed solution of zinc sulfide with a particle size of 1.1 nm and 0.15% by weight of zinc sulfide with a particle size of 2.5 nm are ultrasonically dispersed into a container, and stirred thoroughly to obtain a resin solution.
[0070] 6) A substrate sheet with a thickness of 500 μm after multi-wire cutting was randomly selected, and the processing liquid on the surface was removed by ultrasonic cleaning, and then dried.
[0071] 7) Place the substrate sheet on a coating machine, control the rotation speed of the coating machine at 10,000 rpm, drip the resin solution onto the surface of the substrate sheet, and form a resin layer on the surface of the silicon carbide crystal.
[0072] 8) The silicon carbide crystal coated with the resin layer was placed in a vacuum environment of 0.001 Pa and allowed to stand at 90°C for 10 hours; the temperature was raised to 280°C and cured for 2 hours with the assistance of ultraviolet light, and a transparent resin film with a thickness of 0.25 mm was formed on the surface of the silicon carbide crystal.
[0073] 9) Place the other side of the substrate on a coating machine, repeat the steps 7) and 8) and then send it to an optical microscope for defect analysis.
[0074] Since the resin film is relatively flat, the sample transmittance is about 83% in the visible light range, and the sample surface is flat, so the substrate can be directly optically analyzed to determine the crystal quality without grinding or polishing, saving processing costs and improving efficiency.
[0075] The invention provides a method for improving the transparency of a silicon carbide crystal surface. Phenyl trimethoxysilane, methyl isobutyl ketone, tetrahydrofuran, tetrabutyl titanate and hydrochloric acid are used as raw materials, and then a nano metal compound is added after hydrolysis and condensation to prepare a resin solution that matches the refractive index of the silicon carbide crystal. The resin solution is coated on the surface of the silicon carbide crystal to form a resin layer. The resin layer is cured to form a transparent resin film on the surface of the silicon carbide crystal. The refractive index of the transparent resin film matches the silicon carbide crystal to avoid complex refraction and reflection when electromagnetic waves propagate between the resin and the crystal. The method can obtain a transparent silicon carbide crystal surface without fine grinding and polishing of the silicon carbide crystal, and is convenient for detecting microtubes, impurity inclusions and polymorphic embedding of silicon carbide.
[0076] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for improving the surface transparency of a silicon carbide crystal, characterized in that: The method comprises the following steps: providing a silicon carbide crystal; preparing a resin solution having a refractive index that matches the refractive index of the silicon carbide crystal; applying the resin solution to the surface of the silicon carbide crystal to form a resin layer on the surface of the silicon carbide crystal; Curing the resin layer to form a transparent resin film on the surface of the silicon carbide crystal; The steps of preparing a resin solution having a refractive index that matches the refractive index of the silicon carbide crystal are as follows: Phenyltrimethoxysilane and methyl isobutyl ketone are placed in a reaction container according to a certain mass ratio, and the temperature of the reaction container is maintained at -5 to 5°C; Add a mixture of pure water, hydrochloric acid and tetrahydrofuran in a certain mass ratio dropwise into the reaction container, and stir for 20 to 120 minutes to mix the above components evenly, wherein the stirring speed is controlled at 1 to 100 rpm; Introducing an inert gas into the reaction container, while raising the temperature of the reaction container to 30-90° C., allowing the reaction to proceed for 1-10 hours under the protection of an inert atmosphere; Adding a mixture of tetrabutyl titanate and tetrahydrofuran in a certain mass ratio dropwise into the reaction container for 1 to 10 hours to obtain a mixed solution; The nano-metal compound filler whose mass is 0.1% to 10% of the mass of the mixed solution is dispersed into the reaction container and stirred evenly to obtain a resin solution.
2. The method for improving the surface transparency of silicon carbide crystal according to claim 1, characterized in that: The mass ratio of phenyltrimethoxysilane to methyl isobutyl ketone is 1:2 to 1:8; the mass ratio of pure water, hydrochloric acid and tetrahydrofuran is 1:(0.1 to 1):(2 to 10); the mass ratio of tetrabutyl titanate to tetrahydrofuran is 1:2 to 1:8; and the pH value of the resin solution is 1 to 3.
3. The method for improving the surface transparency of silicon carbide crystal according to claim 1, characterized in that: The steps of applying the resin solution to the surface of the silicon carbide crystal are as follows: placing the silicon carbide crystal on a coating machine; dripping the resin solution onto the surface of the silicon carbide crystal to form a resin layer on the surface of the silicon carbide crystal; wherein, during the coating process, the rotation speed of the coating machine is controlled at 5000 to 15000 rpm.
4. The method for improving the surface transparency of silicon carbide crystal according to claim 1, characterized in that: The steps of curing the resin layer are as follows: placing the silicon carbide crystal coated with the resin layer in a vacuum environment of 0.1 to 0.001 Pa, and standing at a temperature of 50 to 150° C. for 1 to 10 hours; then raising the temperature to 200 to 500° C., and curing for 1 to 10 hours with the assistance of ultraviolet light to form a transparent resin film on the surface of the silicon carbide crystal.
5. The method for improving the surface transparency of silicon carbide crystal according to claim 1, characterized in that: The nano metal compound is any one or more of titanium oxide, zirconium oxide, lead sulfide and zinc sulfide, and the particle size of the nano metal compound is 1 to 50 nm.
6. The method for improving the surface transparency of silicon carbide crystal according to claim 1, characterized in that: The refractive index of the mixed solution is 1.7 to 2.
1.
7. The method for improving the surface transparency of silicon carbide crystal according to claim 1, characterized in that: The refractive index of the resin solution is 1.75 to 2.
75.
8. The method for improving the surface transparency of silicon carbide crystal according to claim 1, characterized in that: The refractive index of the transparent resin film on the surface of the silicon carbide is 1.8-2.7, the thickness of the film is 0.01-5 mm, and the light transmittance is 75-88% within the wavelength range of 400-700 nm.
9. The method for improving the surface transparency of silicon carbide crystal according to claim 1, characterized in that: The transparent resin film is tightly combined with the silicon carbide crystal and has a non-porous region area that accounts for more than 75% of the resin film coverage area.
Citation Information
Patent Citations
A method and apparatus for detecting large-size microtubes in a semiconductor silicon carbide substrate.
CN110361139B
Method for polishing silicon carbide wafer
CN114388347A
Silicon carbide inclusion detection device
CN216082537U
Transmittance improving film
CN102753998A
Three-dimensional printing photocuring ceramic particle and preparation method thereof
CN108285347A